Study on dynamic fracture properties of sandstone under the effect of high-temperature using large-scale sample. (October 2022) - Gao, Weiting; Zhu, Zheming; Ying, Peng; Li, Yaojia; Qiu, Hao; Wang, Meng; Zhou, Lei
Highlights: The influence of high temperature on the physical parameters of sandstone was investigated. The effects of high temperature on the DIT and DPT of sandstone were explored. The dynamic fracture mechanism of sandstone after high temperature treatment was discussed. Abstract: High temperatures are a crucial factor in the drilling of rock and the extraction of geothermal resources, to investigate the change rules of the dynamic fracture mechanism and physical parameters of sandstone under high temperature environment, this study conducted a series of physical parameter measurements on the sandstone treated in a range of temperatures (room temperature to 700 °C) using large single cleavage semicircle compression (LSCSC) sample. According to the experimental results, it can be observed that 400 °C is the threshold for the variation of the physical parameters of sandstone. The mass, P-wave velocity, S-wave velocity, elastic modulus and Poisson' ratio have a significant downward trend with the temperature. The main mineral components of sandstone undergo thermochemical reactions and the variation of quartz is a fundamental cause for the deterioration of sandstone. The dynamic loading test was conducted using a drop hammer impact device and the fractured sample, the dynamic fracture test results indicate that the dynamic crack initiation time (CIT) of the samples is advanced with the temperature, but the crack speed and dynamic fracture toughness decreased with the temperature. Further discussions about SEM images and fractal box dimension of fracture surfaces can be found that with the temperature increases, the proportion of intergranular fractures of sandstone gradually increases, the effect of dynamic loads changes from destroying the grain structure of sandstone to orderly coalescing the micro-cracks in the sandstone.